Retrial queue MMPP/M/N under heavy load condition - Fedorova, Ekaterina A. (Information Technologies and Mathematical Modelling. Queueing Theory and Applications : 20th International Conference, ITMM 2021, named after A. F. Terpugov, Tomsk, Russia, December 1-5, 2021 : revised selected papers)
In the paper, a multi-server retrial queueing system with MMPP arrivals is considered. The service and retrial times are exponentially distributed. The two-dimension stochastic process of number of calls in the orbit and states of service unit is analyzed. The system of Kolmogorov differential equations is composed. The matrix form of the equations in steady-state regime for partial characteristic functions is written. The method of asymptotic analysis under the heavy load condition for its solving is proposed. It is proved that the asymptotic characteristic function of the number of calls in the orbit has the gamma distribution with obtained parameters. Some numerical examples of comparison asymptotic and simulate distributions are presented.